2022
DOI: 10.1155/2022/6280265
|View full text |Cite|
|
Sign up to set email alerts
|

Immunomodulatory Effect of Lycium barbarum Polysaccharides against Liver Fibrosis Based on the Intelligent Medical Internet of Things

Abstract: Lycium barbarum polysaccharide (LBP) is the main active component of Lycium barbarum and has many beneficial effects, including neuroprotection, antiaging, and antioxidation. This study mainly explores the immunomodulatory effect of Lycium barbarum polysaccharides against liver fibrosis based on the intelligent medical Internet of Things. This measure emphasizes that the current effective methods and methods for the treatment of liver cancer are mainly combined treatments of Western medicine and Chinese medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…For example, they increase macrophage phagocytosis, splenic lymphocyte proliferation, antibody secretion from splenocytes, cytotoxic T lymphocyte activity, and IL-2 mRNA expression while decreasing lipid peroxidation ( Gan et al, 2004 ). LBP also has anti-tumor and chemo-protective properties that may lessen Adriamycin’s immunotoxicity and boost its anti-hepatocarcinogenic effects ( Han et al, 2022 ). In the present study, network pharmacology results predicted that the active components of LBP had 146 common core targets with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, they increase macrophage phagocytosis, splenic lymphocyte proliferation, antibody secretion from splenocytes, cytotoxic T lymphocyte activity, and IL-2 mRNA expression while decreasing lipid peroxidation ( Gan et al, 2004 ). LBP also has anti-tumor and chemo-protective properties that may lessen Adriamycin’s immunotoxicity and boost its anti-hepatocarcinogenic effects ( Han et al, 2022 ). In the present study, network pharmacology results predicted that the active components of LBP had 146 common core targets with colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…IoMT research aims to develop applications that leverage AI technologies to assist clinicians in making medical decisions ( Mishra et al, 2022 ). IoMT is used for solving various medical problems such as disease diagnosis ( Verma et al, 2022 ), surgery ( Han et al, 2022 ), and many others. However, IoMT applications encounter various problems, such as the black-box nature of deep learning models.…”
Section: Discussion and Future Directionmentioning
confidence: 99%
“…Polysaccharides against Liver Fibrosis Based on the Intelligent Medical Internet of Tings" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], signifcant concerns were identifed with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
Section: Journal Of Healthcare Engineering Has Retracted the Article ...mentioning
confidence: 99%
“…Journal of Healthcare Engineering has retracted the article titled “Immunomodulatory Effect of Lycium barbarum Polysaccharides against Liver Fibrosis Based on the Intelligent Medical Internet of Things” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%